2001
DOI: 10.1504/ijvd.2001.001931
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of detecting phone-use related driver distraction

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Our study also showed that crossing a red signal was more significantly higher among the drivers who used a mobile phone while driving. De Waard et al (2001) reported that looking at the phone numbers while holding the phone in one hand showed a serious deterioration in driving performance in terms of lane control. The Road and Traffic Department in the State of Qatar has banned the use of handheld mobile phones as of September 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that crossing a red signal was more significantly higher among the drivers who used a mobile phone while driving. De Waard et al (2001) reported that looking at the phone numbers while holding the phone in one hand showed a serious deterioration in driving performance in terms of lane control. The Road and Traffic Department in the State of Qatar has banned the use of handheld mobile phones as of September 2005.…”
Section: Discussionmentioning
confidence: 99%
“…From literature, several studies have proved that in such situations ML approaches can outperform the traditional analytical methods. Moreover, also human's driver mental and physical behavior is non-deterministic [42]- [45].…”
Section: Discussionmentioning
confidence: 99%
“…Selon Reimer, Mehler, Coughlin, Roy et Dusek (2011), le passage d'une simple tâche de conduite à une double tâche augmente la charge de travail (hausse de la fréquence cardiaque moyenne) et dégrade les performances avec une perte du contrôle latéral du véhicule sur la voie. De plus, plusieurs études ont montré que les environnements très complexes menaient à une hausse subjective de la charge de travail et à des dégradations de performances (De Waard, Brookhuis, & Hernandez-Gress, 2001;Baldauf, Burgard, & Wittmann, 2009;Di Stasi et al, 2010).…”
Section: Ii2 Surcharge De Travail En Environnement Complexe Ou Enunclassified